The evolution of the intellectual capital concept and measurement (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2018)
This paper presents two dimensions of intellectual capital (IC): the concept itself and the measurement of IC. In the conceptual section, the importance of IC for competitive advantage and its evolution from practice to academia is discussed. The number and diversity of IC models is considered and their points in common are drawn out: namely, three categories, representing the individual, the collectivity and the relationship perspectives. The importance of social capital for the organization’s survival in the current economic environment is explained, a related bibliometric analysis is reported and an IC model acknowledging this component is suggested. The advent of new kinds of capital is explored and a perspective for their integration with the IC model is proposed. In the measurement section, the foundations of IC measurement and different metrics are discussed. A list of factors to be considered for the choice of the ideal set of metrics is presented. The ResultsBased Management and Accountability Framework is explained and the evaluation of the Canadian Chemical, Biological, Radiological and Nuclear Research and Technology knowledge management initiative is given as an example. Recommendations to the reader on how to build their own assessment strategy are made and, in conclusion, future research venues are suggested.Keywords: Intellectual capital. Intellectual capital models. Intellectual capital bibliometrics. Google trends. Intellectual capital metrics. Results-based management and accountability framework. Logic model.Link: http://revista.ibict.br/ciinf/article/view/4054/3573